2021
DOI: 10.52403/ijhsr.20211048
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Incidence of Diarrhoea in Children Aged 6-24 Months Who Receive Exclusive and Non-Exclusive Breastfeeding

Abstract: Diarrhoea is still a problem for public health in developing countries, especially in Indonesia. The incidence of diarrhoea primarily affects infants in the 6-24 months age group because the infants start to obtain non-milk supplementary food in this age group, consequently increasing the risk of getting infected due to the consumption of germ-contaminated food. Breast milk contains required antibodies, and breastfed infants tend to have a more stable immune system than formula-fed infants. Most infant formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The present study showed that in general, most diarrheal cases (83.3%) occurred in the 1 st year of life (Table 1). Two different studies showed that in comparison to the 2 nd year of life, diarrhea is more common in the 1 st year, especially 6-11 months, and they attributed these results to the combined effect of lowering maternal antibody levels, the infant's lack of active immunity, the introduction of food that may be contaminated with fecal bacteria and direct contact with human or animal feces when the infant begins to crawl [17], [18], In addition to being diarrhea more common in the 1 st year of life, AOMD is significantly more common at this age (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that in general, most diarrheal cases (83.3%) occurred in the 1 st year of life (Table 1). Two different studies showed that in comparison to the 2 nd year of life, diarrhea is more common in the 1 st year, especially 6-11 months, and they attributed these results to the combined effect of lowering maternal antibody levels, the infant's lack of active immunity, the introduction of food that may be contaminated with fecal bacteria and direct contact with human or animal feces when the infant begins to crawl [17], [18], In addition to being diarrhea more common in the 1 st year of life, AOMD is significantly more common at this age (Table 1).…”
Section: Discussionmentioning
confidence: 99%